Chemical synthesis of diglucosyl diacylglycerols utilizing glycosyl donors with stereodirecting cyclic silyl protective groups. (1st September 2019) - Takato, Koichi; Kurita, Motoki; Yagami, Nahoko; Tanaka, Hide-Nori; Ando, Hiromune; Imamura, Akihiro; Ishida, Hideharu
Abstract: Chemical syntheses of the bacterial diglucosyl diacylglycerols 1-heptadecanoyl-2-pentadecanoyl-3- O -[6- O -(β-d-glucopyranosyl)-β-d-glucopyranosyl]- sn -glycerol and 1-( cis -13-octadecenoyl)-2-palmitoyl-3- O -[2- O -(α-d-glucopyranosyl)-α-d-glucopyranosyl]- sn -glycerol are described. The syntheses feature the stereoselective construction of glycosidic linkages in glycosylation reaction by utilizing glycosyl donors with stereodirecting cyclic silyl protective groups. The 1, 1, 3, 3-tetraisopropyldisiloxane-1, 3-diyl (TIPDS) group was used for formation of the β-glycosidic linkage, while the di- tert -butylsilylene (DTBS) group was used for α-linkage formation. The silyl protective groups were chemoselectively cleavable without affecting acyl functionalities on the glycerol moiety and proved effective for the synthesis of diacylglycoglycerolipids. Graphical abstract: Image 1 Highlights: Diglucosyl diacylglycerols (DGDGs) occur widely in nature. Efficient chemical syntheses of two representative bacterial DGDGs were achieved. Stereodirecting effects of cyclic silyl protective groups delivered target DGDGs.